2010
DOI: 10.4314/ijhr.v2i2.55421
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial susceptibilities of salmonellae isolated from food handlers and cattle in Lagos, Nigeria

Abstract: an online international journal allowing free unlimited access to abstract and full-text of published articles. The journal is devoted to the promotion of health sciences and related disciplines (including medicine, pharmacy, nursing, biotechnology, cell and molecular biology, and related engineering fields). It seeks particularly (but not exclusively) to encourage multidisciplinary research and collaboration among scientists, the industry and the healthcare professionals. It will also provide an international… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
33
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 16 publications
11
33
0
3
Order By: Relevance
“…Primer 1254 did not produce any discriminatory pattern amongst the Salmonella isolates and obviously no typing was possible. This result is in consonance with studies conducted in Lagos, Nigeria by Smith et al (2011) and Akinyemi et al (2014). These investigators demonstrated that RAPD-PCR using primer 1254 did not discriminate among Salmonella isolates.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Primer 1254 did not produce any discriminatory pattern amongst the Salmonella isolates and obviously no typing was possible. This result is in consonance with studies conducted in Lagos, Nigeria by Smith et al (2011) and Akinyemi et al (2014). These investigators demonstrated that RAPD-PCR using primer 1254 did not discriminate among Salmonella isolates.…”
Section: Discussionsupporting
confidence: 86%
“…The use of DNA-based typing methods is becoming increasingly important in epidemiological survey and differentiation of Salmonella species. Some of these methods include pulsed field gel electrophoresis (PFGE) (Mohand et al, 1999;Kubota et al, 2005), PCR ribotyping (Lagatolla et al, 1996), automated nuclease PCR assay (Hoorfar et al, 2000) and random amplification of polymorphic DNA (RAPD) (Shangkuan and Lin, 1998;Smith et al, 2011). RAPD-PCR does not require any specific knowledge of the target DNA sequence, making it a flexible and powerful tool with general applicability.…”
Section: Introductionmentioning
confidence: 99%
“…3 Food contamination with antibiotic-resistant bacteria can be a major threat to public health, and the resistance issue may be a challenging task in infection control. 4,5 The over crowed living conditions and inadequate hygiene facilities of the majority of these subjects results in poor sanitary conditions. Vendors of ready-toeat food constitute a major source of food health risk, especially through fecal-oral transmission of pathogens, and vendor related risk is particularly high in poor resource communities.…”
Section: Introductionmentioning
confidence: 99%
“…Vendors of ready-toeat food constitute a major source of food health risk, especially through fecal-oral transmission of pathogens, and vendor related risk is particularly high in poor resource communities. 6,7 The World Health Organization estimates 16 million new cases and 600,000 deaths of typhoid fever were estimated each year. 8 The studies suggested that problem associated with safety of street foods are real and need to be addressed to protect consumers.…”
Section: Introductionmentioning
confidence: 99%
“…The supernatant containing the DNA was transfer to another tube. The purity of the extracted DNA was estimated using a Nanodrop spectrophotometer (Smith et al, 2015).…”
Section: Isolation and Identification Of Salmonella Sppmentioning
confidence: 99%